Transformation of Student Management in Increasing Student Participation in Non Academic Activities - Rini Riyanti; R Supyan Sauri; Saeful Anwar (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the effectiveness of student management in supporting non-academic activities, identify the main challenges faced, and formulate strategies to increase student participation at SMAN 1 Sukadana and SMAN 1 Baregbeg. The study uses a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation using triangulation techniques to ensure validity. Research informants included the principal, vice principal for student affairs, extracurricular advisors, student council administrators, and active students. Data analysis was carried out through the stages of reduction, presentation, and contextual conclusion drawing. Previous studies have confirmed that non-academic participation contributes significantly to strengthening students' soft skills, discipline, and identity formation. The findings show that the effectiveness of student affairs management is determined by five main indicators, namely student-needs-based planning, consistent program implementation, active student participation, improved academic and non-academic achievement, and continuous evaluation and feedback. Both schools succeeded in increasing student participation to 76% (Sukadana) and 72% (Baregbeg) through program diversification, community involvement, and optimization of communication media. However, challenges such as limited guidance staff, funds, internal communication, and learning time still hamper implementation. Adaptive, collaborative, and participatory student management has been proven to increase student participation in non-academic activities and strengthen character education. Effective strategies include program diversification according to student interests, creative promotion, strengthening the capacity of supervisors, involving parents and the community, and a fair reward system. Thus, the transformation of student management is an urgent need to create a holistic, inclusive, and sustainable school.